Penghulu dan Kyai di Karesidenan Cirebon Semangat Keberagamaan dan Berpolitik pada Awal Abad ke-20 - Imas Emalia (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2006)
History of the Indonesian Islamic devlopment in the dutch colonial era is very interisting to be researched. one of them is about the role of the Muslim Scholars (kyai and penghulu). Penghulu when becames colonial bureaucrat is critized by kyai because he defends a colonial interest while kyai fights them